Inherently Safer Automation. Issue 1 (1st February 2018) - Summers, Angela
Abstract : Inherently safer design and functionally safe design go hand‐in‐hand in ensuring safe operation. As processes go from conceptual to existing installations, the opportunities to apply the inherently safer strategies to the process design become constrained by cost and practicality. A wider perspective shows that the inherently safer strategies can be used to create instrumented systems that have less potential for dangerous failure, whether the failure occurs due to safeguard design, to a support system disruption or to human error. One might argue that the application of these strategies to automation can only make a process safer, rather than inherently safer. However, when such strategies are applied systematically across the site, the resulting design and management practices become part of "the way things are done" and result in an inherently safer process operation. This article discusses the cost and sustainability of different instrumented safeguard options to provide a broader perspective on why a design team might choose one layer over another when the risk reduction seems similar. Initial choice is often driven by considerations of capital and operating cost, since these factors weigh heavily in determining whether a project is funded. System complexity must also be considered because long‐term sustainability and reliability is dependent on humans not introducing errors into the system. Finally, inherently safer terminology is defined from an automation perspective and numerous examples are given on how each strategy can be applied to automation. © 2018 American Institute of Chemical Engineers Process Process Saf Prog 37:31–36, 2018